(untitled) (Asian-Australasian Journal of Food Safety and Security, 2019)
An experiment was carried out to comparative analysis of nutritional quality of different fish feed from different feed dealers and industries in greater Noakhali region and to compare the values with those provided by the manufacturers. The feed samples were collected from different feed industries and dealer’s shop of these region. Feed samples were collected during 10 August to 5 September, 2016. The collected feed samples were stored and analyzed in the Fish Nutrition Laboratory of the Department of Aquaculture in the Faculty of Fisheries, Bangladesh Agricultural University (BAU), Mymensingh for proximate composition (moisture, ash, crude protein, crude lipid, crude fiber, carbohydrate) following standard methods. Results showed that there was significant variation between analyzed and company provided nutritive values of different feeds. Some feed samples have low moisture level (difference 0.7 to 3.3%). Ash content of the experimental samples also show a variety of results compared to their labeled composition. Only some feed have more values to the company provided values, such as, Mega starter (12.13%) and Bengal grower (12.75) proportion with 12%. Some feed contains more difference range of 6.01% more than labeled values is RP feed (20.01%). Maximum feed samples had lower crude protein (difference 0.05 to 4.65%) than the company provided protein values. However, only crude protein of Bengal finisher (29.95%) and Aftab grower (28.07%) feeds were found to be almost same to the company provided nutritive values (30% and 28%). The lipid, ash and carbohydrates contents of the experimental samples also have a difference range. The highest lipid values are available in Provita starter (9.76%) and lowest values containing feed Setu grower (4.33%). The highest carbohydrates content in the feed Provita starter (36.84%). The findings of this study demonstrated that low quality commercial fish feeds were supplied to the fish farmers by majority of feed companies. Therefore, the study will generate some information to the farmers which will help to choose the best feed for their aquaculture production. Asian Australas. J. Food Saf. Secur. 2019, 3(1), 1-14